Challenges of scientific knowledge visualization in publication productivity of the university academic staff - Kabanova N. N. Natalia Nikolaevna; Pankova N. M. Nataliya Mikhailovna; Hollenbeck J. E. James; Prokhorova K. E. Kristina (2016, 2016)
Title screen